Nie(do)czytany Gomulicki – nowelistyka poety. Prolegomena - Zajkowska, Joanna (Poznańskie Studia Polonistyczne. Seria Literacka, 2024)
The paper discusses three volumes of Wiktor Gomulicki’s short stories: Kolorowe obrazki (Colourful pictures), Z otchłani (From the abyss) and Przy słońcu i przy gazie (By the sunlight and gaslight). The author proves how the style and theme of short stories changes in time. The article proposes a new interpretation of Przy słońcu i przy gazie using the category of arabesque which was one of the genres popular in nineteenth-century European and Polish literature.